Play along: effects of music and social interaction on word learning - Verga, Laura; Bigand, Emmanuel; Kotz, Sonja A. (Frontiers in Psychology, 2015)
Learning new words is an increasingly common necessity in everyday life. External factors, among which music and social interaction are particularly debated, are claimed to facilitate this task. Due to their influence on the learner’s temporal behavior, these stimuli are able to drive the learner's attention to the correct referent of new words at the correct point in time. However, do music and social interaction impact learning behavior in the same way? The current study aims to answer this question. Native German speakers (N = 80) were requested to learn new words (pseudo-words) during a contextual learning game. This learning task was performed alone with a computer or with a partner, with or without music. Results showed that music and social interaction had a different impact on the learner’s behavior: Participants tended to temporally coordinate their behavior more with a partner than with music, and in both cases more than with a computer. However, when both music and social interaction were present, this temporal coordination was hindered. These results suggest that while music and social interaction do influence participants’ learning behavior, they have a different impact. Moreover, impaired behavior when both music and a partner are present suggests that different mechanisms are employed to coordinate with the two types of stimuli. Whether one or the other approach is more efficient for word learning, however, is a question still requiring further investigation, as no differences were observed between conditions in a retrieval phase which took place immediately after the learning session. This study contributes to the literature on word learning in adults by investigating two possible facilitating factors, and has important implications for situations such as music therapy, in which music and social interaction are present at the same time.